The impact of cooperative learning method on Yemeni adult students’ knowledge of global issues vocabulary - Kamariah, Yunus; Lamis Abdulkarim, Al-Shuga'a; Mohammed Abdulgalil, Abugohar (2020)
The cooperative learning method is one of the most effective student-centered learning methods used in teaching English language classes. It is an updated and effective pedagogic method that should be integrated into classrooms. The previously reviewed studies showed that the use of cooperative learning method may improve students’ knowledge of the language. This paper aims at investigating the impact of cooperative learning methods on Yemeni adult students’ knowledge of global issues vocabulary. The study employed an experimental method research design where the quantitative data collection method was conducted. A pretest and posttest (of the same test) were administered to the 25 respondents in the experimental group and the other 25 respondents in the control group. The Statistical Package for Social Sciences (SPSS) version 25.0 was used to analyse the difference between the two groups’ performance using the t-test. Results showed that the students in the experimental group performed significantly better than the students in the comparison group in the required tasks relating to global issues vocabulary knowledge. Findings also indicated that the cooperative learning method had positive effects on students’ vocabulary knowledge in classrooms. The participants gained confidence and their language skills were improved. Social skills like leadership, decision-making, trust-building, communication, and conflict-management skills were also developed. The study concludes that cooperative learning contributes to cognitive growth, increased autonomy and productivity of adult learners. The cooperative learning method should be integrated into English language classrooms to improve the growth and productive knowledge of students at the tertiary level.